The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.1108/cr-12-2014-0040
|View full text |Cite
|
Sign up to set email alerts
|

Complementing clusters: a competitiveness rationale for infrastructure investments

Abstract: Purpose – The purpose of this paper is to present a novel application of cluster theory and cluster methodology to evaluate large infrastructure investments. The complementing clusters approach, which builds on the notion of infrastructure as connecting isolated “economic islands”, is able to assess the potential for value creation effects of new infrastructure investment. Design/methodology/approach – The author uses simulation analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…So that enterprises can achieve the goal of improving performance through these advantages. In addition, the competition among enterprises in the cluster is gradually intensified, which forces the innovation ability of enterprises in the cluster to be enhanced, and the performance of enterprises will be improved to a certain extent [52]. Research on the relationship between entrepreneurship, enterprise cluster and performance concluded that the knowledge-based agglomeration of enterprises positively impacts enterprise performance [53].…”
Section: Hypothesis 221 the Relationship Between Industry Cluster And...mentioning
confidence: 99%
“…So that enterprises can achieve the goal of improving performance through these advantages. In addition, the competition among enterprises in the cluster is gradually intensified, which forces the innovation ability of enterprises in the cluster to be enhanced, and the performance of enterprises will be improved to a certain extent [52]. Research on the relationship between entrepreneurship, enterprise cluster and performance concluded that the knowledge-based agglomeration of enterprises positively impacts enterprise performance [53].…”
Section: Hypothesis 221 the Relationship Between Industry Cluster And...mentioning
confidence: 99%
“…The nature of the literature on industry clusters, with some notable exceptions (Delgado et al, 2010;Sasson and Reve, 2015) tends toward a more qualitative approach, emphasizing a more in-depth understanding of industry linkages (Titze et al, 2011), the behavior of individual firms within competitive industry clusters, and elements of industrial organization (Kubis et al, 2012). Thus, it seems reasonable to investigate the role of transportation networks and transportation policy in supporting the growth of clusters in the same fashion.…”
Section: Transportation Agglomeration and Industry Clustersmentioning
confidence: 99%
“…Clusters can be defined as "geographic concentrations of interconnected companies and institutions in a particular field" (Porter, 1998). Although, in particular, economic geographers had been studying clusters already for an extended period before that, Porter's (1990) contribution increased the popularity and attention of the concept of clusters in several fields, and remains a current topic (Keller et al, 2015;O'Dwyer et al, 2015;Sasson and Reve, 2015;Wilson et al, 2014). For example, clusters can be viewed as enhancing the competitiveness of an industry in a location (Davies, 2001;Delgado et al, 2014) and is linked to theories about networks (Bryson et al, 1993;Lundberg, 2010;Niu et al, 2008), as well as firm aspects (Niu, 2010;Niu et al, 2012), and clusters have also frequently been linked to the performance of a region (Blair, 2004;Feldman and Tavassoli, 2014;Porter, 2003).…”
Section: Introductionmentioning
confidence: 99%